Association between perceived racial discrimination and hypertension: findings from the ELSA-Brasil study - NOBRE, Aline Araújo (Escola Nacional de Saúde Pública Sergio Arouca, Fundação Oswaldo Cruz, 2019)
“Pardos” and blacks in Brazil and blacks in the USA are at greater risk of developing arterial hypertension than whites, and the causes of this inequality are still little understood. Psychosocial and contextual factors, including racial discrimination, are indicated as conditions associated with this inequality. The aim of this study was to identify the association between perceived racial discrimination and hypertension. The study evaluated 14,012 workers from the ELSA-Brazil baseline population. Perceived discrimination was measured by the Lifetime Major Events Scale, adapted to Portuguese. Classification by race/color followed the categories proposed by Brazilian Institute of Geography and Statistics (IBGE). Hypertension was defined by standard criteria. The association between the compound variable - race/racial discrimination - and hypertension was estimated by Poisson regression with robust variance and stratified by the categories of body mass index (BMI) and sex. Choosing white women as the reference group, in the BMI < 25kg/m2 stratum, “pardo” women showed adjusted OR for arterial hypertension of 1.98 (95%CI: 1.17-3.36) and 1.3 (95%CI: 1.13-1.65), respectively, whether or not they experienced racial discrimination. For black women, ORs were 1.9 (95%CI: 1.42-2.62) and 1.72 (95%CI: 1.36-2.18), respectively, for the same categories. Among women with BMI > 25kg/m2 and men in any BMI category, no effect of racial discrimination was identified. Despite the differences in point estimates of prevalence of hypertension between “pardo” women who reported and those who did not report discrimination, our results are insufficient to assert that an association exists between racial discrimination and hypertension.